THE IDENTITY OF KAZAKHSTANI YOUTH: IMPACT OF GLOBALIZATION AND NEOTRADITIONALISM - KARIPBAYEV, Baizhol (CENTRAL ASIA AND THE CAUCASUS, 2021)
The article analyzes the value orientations of modern student youth in Kazakhstan that influence the formation of their identity. Based on the analysis of this social group’s value alignments, the article attempts to determine the vital problem areas in the formation of the character of young people as those capable of taking responsibility for their own destiny and the destiny of their country. Special attention is heeded to ethnic, religious and civic identities. The ratio of civil and ethnic identities among Kazakhstani student youth is assessed. A growth tendency in the norms of individualism and indifference to traditional forms of identity is revealed. Particular attention is paid to the influence of traditional and modernization values on the self-awareness of Kazakhstani youth. This research perspective was selected deliberately. The current state of public relations—both global, and Kazakhstani in particular—is determined by active ambiguous, multi-directional transformation processes. Under these circumstances, the issue of identity becomes especially acute for young people, and a search for sources of worldviews ensues to help young people formulate and self-actualize their own essence and to construct their own view of the world. In the course of this search, it is crucial to avoid becoming an object of various kinds of ideological, spiritual, ideological manipulation and recruiting. The modern contemporary social reality engenders a wide variety of spiritual practices, ideological revelations and political modules. It is essential for a young person to make the right choice based on objective knowledge and understanding. Under the circumstances, a special responsibility is imposed on the education system. Unfortunately, the modern higher education system in Kazakhstan pays special attention to the rigid specialization of graduates as part of the current vigorous reforms. Purely professional training is becoming a priority, while the issues of socio-humanitarian, ideological training of our future specialists remain on the margins of the educational system, which, in turn, impedes their successful socialization. It is in these epistemological coordinates that this article was prepared. The article is based on the data obtained through a sociological study conducted in 2019 as part of the project “Formation of the Concept of Religious Tolerance and Ethnic Consolidation in Educational Formats of Modern Kazakhstan.”